Phrygian Fibulae from Gordion - Muscarella, Oscar White
Ph. D.; Supervisor: Rodney S. Young; University Microfilms Order No. 66-288. Microfilm $3.20; Xerography $11.25; Dissertation Abstracts 26/9 (Ann Arbor, Mich., March 1966) 5388.